Análisis de Genes relacionados con la respuesta Inmunitaria de los Parásitos (céstodos) para el Diseño de Vacunas de ADN. - Tutaxi Ríos, Paola Alexandra (2020)
Analyzing of the genes related to the parasite’s immune response at the cestodes was developed WAS done in this research, since having the substantiated information can be used by students, teachers and researchers, for the development of a vaccine and thus be able to fight them. For that, will merge information on the genetic sequence of each ones from the different domestic species such as: canines, felines, bovines, swine, sheep, goats, South American camelids, equines, lagomorphs, guinea pigs, birds (hens, turkeys, geese and ducks), to later be analyzed through the National Center for Biotechnology Information (NCBI), which is in charge of grouping essential databases into three large sectors: (Literature Databases, Molecular Databases and Genomes). The analysis carried out on domestic animal species against the different cestode parasites, the following genes that are related to immunity can be mentioned: Canines: The genes Th1, Th2, EgAgB, NC2, To45W, Genotype D. caninum, Tbx6 (transcription factor); Felines: Th2 and feline genotype of D. caninum; Cattle: Th2, NC1, NC2, EgAgB, Ts45W, Pigs: Th2 IL-4 / IL-5, EgAgB; Horses: Th1, EgAgB, Sheep: Th2, EgAgB, NC1, NC2, To45W, Tbx6, Camelids: Th2, NC1, NC2, To45W; Goats: NC2, Tbx6; Guinea pigs: Th1, EgAgB, Th2; Lagomorphs: Th1, EgAgB; Poultry: RT10 CDNA (chickens, turkeys and geese). With this specific and necessary information obtained will help researchers to develop a DNA vaccine that fights these parasites and thus creates immunity on the part of the animals, so that when they are infected by some of them the animal antibodies act and attack the parasite, through this it will be possible to reduce the deworming protocols that are routinely carried out through the deworming calendar, having to understand that Conventional injectable have not allowed to eliminate the parasite either because the antiparasitic are in a general way as well as because of the egg morphology, evolutionary cycle and the resistance that these may have to the drug, which is why it can cause subclinical cases to chronic cases that slowly deteriorate the health of the animal and extreme cases that can reach to cause death.